The Jungian Shadow Archetype in Poe’s Gothic “The Tell-Tale Heart” (1843) and “The Black Cat” (1843) - Yagoubi, Wiam Fatima Zahra; BOUMOUS, Moufida (University of Ammar Theledji -Laghouat, 2020)
Every dark comedies, adventures and science fiction, they all clearly exhibit any author’s obsession with the functioning of the human mind. Complex personalities are the most prominent characteristics of gothic writings. According to Jung, the archetype’s existence within the human psyche is to maintain stability between good and evil. Hence, this work aims to analyze the characters’ behaviors and their influence on “The Tell-Tale Heart” (1843) and “The Black Cat” (1843). This study is an analytical descriptive approach to the aforementioned short stories with regard to Jungian shadow archetype to interpret the psychology of the characters and their behaviors. In three chapters, this study tries to analyze Poe’s allegorical short stories highlighting the narrator’s irrational anxiety and shedding light on Edgar Allan Poe’s motives behind the use of characters’ disturbed psyches in his works “The Tell-Tale Heart”(1843) and “The Black Cat”(1843).